Subxiphoid thoracoscopic thymectomy in a young female with seropositive Myasthenia Gravis: A case report - Tiwari, Manoj; Thakur, Binay; Shun, Zhenqing; Khatiwada, Sagar; Bhattarai, Sachee (Nepalese Journal of Cancer, 2024)
Case: Myasthenia Gravis (MG) is an autoimmune disease that occurs at the neuromuscular junction and characterized by weakness of voluntary skeletal muscles which may be generalized or localized with an incidence of 4.1 to 30 cases per million person-years. MG is diagnosed clinically and by measuring the level of acetylcholine receptor antibodies, Muscle specific kinase antibodies and Low-density lipoprotein receptor related protein-4 antibodies. Patient is managed conservatively with cholinesterase inhibitor (pyridostigmine), prednisone, Mycophenolate mofetil and surgically by thymectomy. Here we present a case of a 27-year female who was known case of seropositive Myasthenia gravis for five years who underwent a novel technique of subxiphoid thymectomy.